Cortical profiles of numerous psychiatric disorders and normal development share a common pattern - Cao, Zhipeng; Cupertino, Renata B.; Ottino-Gonzalez, Jonatan; Murphy, Alistair; Pancholi, Devarshi; Juliano, Anthony; Chaarani, Bader; Albaugh, Matthew; Yuan, Dekang; Schwab, Nathan; Stafford, James; Goudriaan, Anna E.; et al. (Molecular psychiatry, 2023)
The neurobiological bases of the association between development and psychopathology remain poorly understood. Here, we identify a shared spatial pattern of cortical thickness (CT) in normative development and several psychiatric and neurological disorders. Principal component analysis (PCA) was applied to CT of 68 regions in the Desikan-Killiany atlas derived from three large-scale datasets comprising a total of 41,075 neurotypical participants. PCA produced a spatially broad first principal component (PC1) that was reproducible across datasets. Then PC1 derived from healthy adult participants was compared to the pattern of CT differences associated with psychiatric and neurological disorders comprising a total of 14,886 cases and 20,962 controls from seven ENIGMA disease-related working groups, normative maturation and aging comprising a total of 17,697 scans from the ABCD Study® and the IMAGEN developmental study, and 17,075 participants from the ENIGMA Lifespan working group, as well as gene expression maps from the Allen Human Brain Atlas. Results revealed substantial spatial correspondences between PC1 and widespread lower CT observed in numerous psychiatric disorders. Moreover, the PC1 pattern was also correlated with the spatial pattern of normative maturation and aging. The transcriptional analysis identified a set of genes including KCNA2, KCNS1 and KCNS2 with expression patterns closely related to the spatial pattern of PC1. The gene category enrichment analysis indicated that the transcriptional correlations of PC1 were enriched to multiple gene ontology categories and were specifically over-represented starting at late childhood, coinciding with the onset of significant cortical maturation and emergence of psychopathology during the prepubertal-to-pubertal transition. Collectively, the present study reports a reproducible latent pattern of CT that captures interregional profiles of cortical changes in both normative brain maturation and a spectrum of psychiatric disorders. The pubertal timing of the expression of PC1-related genes implicates disrupted neurodevelopment in the pathogenesis of the spectrum of psychiatric diseases emerging during adolescence.
Online veröffentlicht: 15. November 2022
Gesehen am 17.06.2024
Mitlgieder des IMAGEN Consortium: Tobias Banaschewski, Arun L.W. Bokde, Sylvane Desrivières, Herta Flor, Antoine Grigis, Penny Gowland, Andreas Heinz , Rüdiger Brühl, Jean-Luc Martinot, Marie-Laure Paillère, Martinot, Eric Artiges, Frauke Nees, Dimitri Papadopoulos Orfanos, Tomáš Paus, Luise Poustka, Sarah Hohmann, Sabina Millenet, Juliane H. Fröhner, Lauren Robinson, Michael N. Smolka, Henrik Walter, Jeanne Winterer, Gunter Schumann, Robert Whelan and Hugh Garavan
Mitglieder der ENIGMA ADDICTION WORKING GROUP: Zhipeng Cao, Renata B. Cupertino, Jonatan Ottino-Gonzalez, Alistair Murphy, Devarshi Pancholi, Anthony Juliano, Anna E. Goudriaan, Kent Hutchison, Chiang-Shan R. Li, Maartje Luijten, Martine Groefsema, Reza Momenan, Lianne Schmaal, Rajita Sinha, Ruth J. van Holst, Dick J. Veltman, Reinout W. Wiers, Bernice Porjesz, Tristram Lett, Ravi R. Bhatt, Alyssa Zhu, Patricia Conrod, Neda Jahanshad, Paul M. Thompson, Scott Mackey and Hugh Garavan